Multi-axial fatigue numerical crack propagation in cruciform specimens (Fracture and Structural Integrity, 2019)
Two cracks, initiated from the opposite tips of a central notch inclined by 45°, were considered in cruciform specimens made of Ti6246. A static load was applied to a cruciform arm while a cyclic load was applied along the other arm.Fatigue propagation of cracked specimens was performed by means of Dual Boundary Element Method (DBEM) and Finite Element Method (FEM) codes. For crack path assessment, the Minimum Strain Energy Density (MSED) and the Maximum Tensile Stress (MTS) criteria were adopted in DBEM and FEM approaches, respectively. Moreover, the J and M integrals’ formulations were used to evaluate the SIFs along the crack fronts for DBEM and FEM codes, respectively. Crack-growth rates were predicted by using a Walker law, calibrated on mode I fracture experimental data.A good agreement between numerical and experimental crack paths was obtained.
Keywords: Cruciform specimen; Multiple cracks; DBEM; crack path; HCF